Accidentally diagnosed transitional cell papilloma of the lacrimal sac - Dave, Tarjani Vivek (Saudi J Ophthalmol, 2017)
Lacrimal sac tumors are extremely rare but can be life threatening. Seventy percent of lacrimal sac tumors are of epithelial origin. Inverted transitional cell papilloma of the lacrimal sac is a rare epithelial sinonasal tumor of benign etiology with local invasion and malignant potential. These lesions may remain undiagnosed or may present with signs and symptoms of dacryocystitis or may transform to transitional cell carcinomas. Most lesions are diagnosed intra-operatively while performing a dacryocystorhinostomy. Biopsy and histopathological examination of mass lesions arising from the lacrimal sac helps in timely management of these rare tumors.